An Integrated Holistic Approach Using Music Therapy and Hypnotherapy to Reduce Anxiety in Pregnant Women for Childbirth Preparation - Yunida Turisna Octavia; Inggrit Puspita Sari; Eva Kartika Hasibuan; Sri Purwanti (Caring: Indonesian Journal of Nursing Science, 2025)
The maternal mortality rate in North Sumatra in 2023 remained high at 78.82 per 100,000 live births. Anxiety during late pregnancy, with a prevalence of 18.2–24.6%, increases the risk of maternal and neonatal complications. Although non-pharmacological interventions such as music therapy and hypnotherapy are widely used, evidence regarding the effectiveness of their combined application remains limited. This study aimed to evaluate the effectiveness of integrating hypnotherapy and music therapy in reducing anxiety among pregnant women.  A quasi-experimental design with intervention and control groups without randomization was conducted. The study involved 30 pregnant women in their second to third trimesters selected using purposive sampling (intervention group n=15; control group n=15). The intervention consisted of four sessions of guided hypnotherapy relaxation accompanied by slow-tempo classical instrumental music over a two-week period, with each session lasting 35–40 minutes. Anxiety levels were measured using the Hamilton Rating Scale for Anxiety (HRS-A) before and after the intervention, and data were analyzed using the paired t-test. The results showed a significant reduction in anxiety scores in the intervention group, decreasing from 27.07 to 15.20 (p<0.001), while the control group showed no significant change (30.33 to 30.00; p=0.96). The reduction in anxiety was attributable to the intervention. The integration of hypnotherapy and music therapy was effective in reducing anxiety prior to childbirth and demonstrated better outcomes than the control group. This approach can be recommended as a comprehensive non-pharmacological intervention in prenatal care programs. Keyword: Music therapy, Hypnotherapy, Pregnancy, Anxiety, Childbirth